1984
DOI: 10.1080/15287398409530621
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic, pathologic, and immunotoxic effects of 2,4‐dichlorophenol in rats

Abstract: 2,4-Dichlorophenol (DCP) is a drinking and waste-water contaminant formed by the spontaneous reaction of chlorine with phenols following chlorination of water for disinfection and deodorization. Rats were exposed to 0, 3, 30, or 300 ppm DCP in drinking water either in utero or for 12 wk postnatally following in utero exposure. Toxicity to DCP was assessed by organ and body weight changes, histopathology, and effects on reproduction and immunocompetence. Reproductive parameters measured included conception, lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…2,5-dichlorophenol, the primary metabolite of p-dichlorobenzene, is common in US populations [1]. Exposure to high doses of 2,4-chlorophenol in laboratory animals causes immunological and liver related effects, in addition to smaller litters and offspring with decreased birth weight [48]. There are a couple of technical manuscripts devoted to analytical method development that report rarely detecting 2,4- and 2,5-dichlorophenol in milk [39, 49].…”
Section: Discussionmentioning
confidence: 99%
“…2,5-dichlorophenol, the primary metabolite of p-dichlorobenzene, is common in US populations [1]. Exposure to high doses of 2,4-chlorophenol in laboratory animals causes immunological and liver related effects, in addition to smaller litters and offspring with decreased birth weight [48]. There are a couple of technical manuscripts devoted to analytical method development that report rarely detecting 2,4- and 2,5-dichlorophenol in milk [39, 49].…”
Section: Discussionmentioning
confidence: 99%
“…2,4-DCP is a lipophilic chlorinated phenol from the phenoxy acetic acid herbicide family that is frequently utilized in the production of herbicides and insecticides (Exon et al 1984;Magnoli et al 2020;Zhang et al 2018). Excessive doses of herbicides are frequently employed due to weed resistance, resulting in biological buildup even with shortterm exposure (Magnoli et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2,4-DCP can be generated by the deformation of pesticides, primarily phenoxy herbicides like 2,4-dichlorophenoxyacetic acid, as well as antibacterial and antifungal chemicals like triclosan, which is also a byproduct of municipal drinking water and industrial effluent chlorination (Bukowska et al 2016;Ye et al 2014). Because of these chemicals' lipophilic characteristics, if they reach the environment, they can accumulate in the bodies of plants and animals, eventually entering the food chain and endangering health (Ding et al 2020;Exon et al 1984;Yueh and Tukey 2016;Parastar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that 2,4-DCP can be formed as a degradation product of 2,4-D (Zona et al, 2002) and that phenols and chlorines may naturally react with each other to form 2,4-DCP on disinfection of drinking water or with deodorization of pollutant water (Exon et al, 1984).…”
Section: Introductionmentioning
confidence: 99%